2019
DOI: 10.1038/s41598-019-40606-6
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α overexpression partially rescues impaired oxidative and contractile pathophysiology following volumetric muscle loss injury

Abstract: Volumetric muscle loss (VML) injury is characterized by a non-recoverable loss of muscle fibers due to ablative surgery or severe orthopaedic trauma, that results in chronic functional impairments of the soft tissue. Currently, the effects of VML on the oxidative capacity and adaptability of the remaining injured muscle are unclear. A better understanding of this pathophysiology could significantly shape how VML-injured patients and clinicians approach regenerative medicine and rehabilitation following injury.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 71 publications
8
47
0
Order By: Relevance
“…Given mitochondria’s key role in modulating muscle mass 83 , preventing dysfunction of this organelle could represent a major therapeutic target for rescuing muscle loss in ballistic trauma patients. In support, recent data have shown the PGC-1α signalling axis is disrupted in mice with VML, and that forced expression of PGC-1α using transfection partially rescued muscle strength and oxidative muscle function 151 , which reinforces previous data during disuse atrophy 152 . These data highlight, for the first time, how targeting the mitochondria may play a key role in muscle remodelling post VML.…”
Section: Novel Strategies To Promote Muscle Regeneration After Ballissupporting
confidence: 88%
“…Given mitochondria’s key role in modulating muscle mass 83 , preventing dysfunction of this organelle could represent a major therapeutic target for rescuing muscle loss in ballistic trauma patients. In support, recent data have shown the PGC-1α signalling axis is disrupted in mice with VML, and that forced expression of PGC-1α using transfection partially rescued muscle strength and oxidative muscle function 151 , which reinforces previous data during disuse atrophy 152 . These data highlight, for the first time, how targeting the mitochondria may play a key role in muscle remodelling post VML.…”
Section: Novel Strategies To Promote Muscle Regeneration After Ballissupporting
confidence: 88%
“…We posit that the sequela of VML injury includes impaired whole-body metabolism due to low physical activity and the loss of skeletal muscle tissue. Previous work in animal models of VML has indicated that skeletal muscle specific oxidative function is impaired following injury [ 15 , 16 ], and that the muscle remaining after VML injury has reduced metabolic plasticity compared to healthy, uninjured muscle in response to rehabilitation [ 17 ]. Dysfunction of skeletal muscle metabolism may impede the endogenous healing process and induce further chronic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the integrity of mitochondrial biogenesis signaling in KO muscle, 8 additional untreated mice (n = 4 LM; n = 4 KO) underwent a 30 minute in vivo electrical stimulation protocol to simulate an acute bout of exercise as previously described 15 . Briefly, mice were anesthetized with isoflurane (1.5-2.0%) and platinum-iridium needle electrodes were placed around the sciatic nerve.…”
Section: Acute Stimulation Protocolmentioning
confidence: 99%
“…Mitochondrial function was assessed as previously described 15 Mitochondrial respiration was terminated by the addition of cyanide (2 mM).…”
Section: Mitochondrial Assaysmentioning
confidence: 99%
See 1 more Smart Citation